A Triple Bottom Line Approach for Measuring Supply Chains Sustainability Using Data Envelopment Analysis - Cortes, Alessandro (European Journal of Sustainable Development, 2017)
This paper deals with the issues faced by those who endeavor in measuring sustainability in supply chains (SC) by using a comprehensive approach. Elkington´s Triple Bottom Line (TBL) divide sustainability in three aspects: environmental (E), economic and social (E2S). Firms publish their business (including SC) sustainability impacts through Corporate Social Responsibility reports (CSR). According to Global Reporting Initiative (GRI), a CSR framework, reported information should be sufficiently accurate/detailed towards performance, but reports are rather qualitative. Fast fashion (FF) is a recent phenomenon of production/promotion of cheap/readily disposable clothes. Data Envelopment Analysis (DEA) is the adequate tool to identify best practices regarding sustainability (multidimensional) and supply chains in FF. To allow comparability and tackle lack of quantitative data, TBL clusters (output) are proposed: for each Disclosure, a three layers scoring scale: absence (1), qualitative only (2), 2nd layer plus quantitative (4). This work´s main contribution is the use of DEA as a powerful tool to measure sustainability in SC and the TBL clusters link all dimensions in an innovative way. Keywords: Data Envelopment Analysis, Sustainability, Supply Chains, Triple Bottom Line, Fast Fashion